The Main Determinants of the Balance of Payment of the Kingdom of Saudi Arabia Time Series Analysis from 1981 to 2007 - Mohamed, Ghada Gomaa; Al-Banawi , Nisreen Ismail M. (Current Aspects in Business, Economics and Finance Vol. 8, 2023)
This chapter investigates the impact of theoretically important factors on the status of the balance of payment. The paper utilizes these theoretical concepts to the balance of payment situation in Saudi Arabia from 1981 to 2007. The paper provides interesting implications for decision makers, allowing them to address various implications on the country's balance of payment status by incorporating endogenously distinct macro-variables discussed by the present article. At the same time, they make economic decisions regarding improving the status of the balance of payment.